Allosteric modulation of the cannabinoid 2 receptor confers seizure resistance in mice. (1st May 2021) - Shapiro, Lindsey; Gado, Francesca; Manera, Clementina; Escayg, Andrew
Abstract: Mounting evidence suggests that modulation of cannabinoid 2 receptors (CB2Rs) is therapeutic in mouse models of neurological disorders, including neuropathic pain, neurodegenerative disease, and stroke. We previously showed that reducing CB2R activity increases seizure susceptibility in mice. In the present study, we evaluated the therapeutic potential of the CB2R positive allosteric modulator, Ec21a, against induced seizures in mice. The pharmacokinetic profile of Ec21 demonstrated a similar distribution in brain and plasma, with detection up to 12 h following injection. Ec21a increased resistance to induced seizures in CF1 wild-type mice and mice harboring the SCN1A R1648H human epilepsy mutation. A rotarod test provided evidence that Ec21a does not cause neurotoxicity-induced motor deficits at its therapeutic dose, and seizure protection was maintained with repeated drug administration. The selectivity of Ec21a for CB2R was supported by the ability of the CB2R antagonist AM630, but not the CB1R antagonist AM251, to block Ec21a-conferred seizure protection in mice, and a lack of significant binding of Ec21a to 34 brain-expressed receptors and transporters in vitro . These results identify allosteric modulation of CB2Rs as a promising therapeutic approach for the treatment of epilepsy. Highlights: Ec21a is quickly distributed in the brain and plasma of mice. Ec21a confers seizure resistance in wild-type and Scn1a R1648H/+ mutant mice. Seizure resistance conferred by Ec21a is mediated by cannabinoid 2 receptors. Ec21a-mediated seizure resistance is maintained with repeated drug administration.